International and European in the Accounting System of Romania - Anca Gabriela Turtureanu; Cornelia Elena Tureac (European Financial and Accounting Journal, 2009)
In order to join the European Union, Romania, as well as the other member countries, must accomplish certain criteria, among which we can mention the adopting of the acquis communautaire. Thus, two Guidelines can be considered the basis of the acquis communautaire for the field of the accounting of the corporations: The Fourth Guideline of the Counsel (78/660/EEC) concerning the yearly accounts of the business corporations and the Seventh Guideline of the Counsel (83/349/EEC) concerning the consolidated accounts of the business corporations. Since these two guidelines does not cover the banking industry and the insurance industry, there were adopted two Guidelines in order to cover the problems that appear in the yearly accounts (financial situations) of these two sectors (The Accounts Guideline of the Banking Industry from 1986 and The Accounts Guideline of the of the Insurance Industry from 1991). These four Guidelines are considered to be the fundamental pillars of the acquis, with relevance.
Keywords: M41; 650; Financial reporting; IFRS; Romania; Romanian Accounting Practices